AB0696 DETECTION OF COEXISTING MYOSITIS-SPECIFIC AUTOANTIBODIES WITH LINE AND DOT IMMUNOASSAYS IN PATIENTS WITH IDIOPATHIC INFLAMMATORY MYOPATHIES. (June 2019) - Vulsteke, Jean-Baptiste; Bossuyt, Xavier; Claeys, Kristl G.; Dillaerts, Doreen; Vanhorebeek, Nele; Poesen, Koen; Lenaerts, Jan; Westhovens, Rene; Damme, Philip Van; Blockmans, Daniel; Haes, Petra De; Langhe, Ellen De
Abstract : Background: Myositis-specific autoantibodies (MSAs) can be identified in up to 60% of patients with idiopathic inflammatory myopathies (IIM) (1). Based on previous immunoprecipitation studies, MSAs are considered to be mutually exclusive (1), but detection of coexisting MSAs with line or dot immunoassay (LIA/DIA) has been described (2-3). Objectives: To determine the prevalence of detection of coexisting MSAs with different LIAs/DIAs in patients with IIM, assess the concordance between different assays and describe the clinical phenotype of patients with coexisting MSAs. Methods: Cross-sectional assessment of prevalence of coexisting MSAs as detected by two LIAs (Euroline autoimmune inflammatory Myopathies, Euroimmun, Lübeck, Germany; and ImmcoStripe Myositis advanced LIA, Trinity Biotech, Buffalo, USA) and 1 DIA (12 IgG Dot, alphadia, Mons, Belgium), concordance between these assays and clinical phenotype of patients with coexisting MSAs in a single-center cohort of patients with a diagnosis of one of the subtypes of IIM as diagnosed by the treating physician. Results: Nineteen of 145 patients (12%) had coexisting MSAs on at least one assay: 5 on the DIA (3, 5%) and 5 (3, 5%) and 11 (7, 6%) on the LIA of Euroimmun and Trinity Biotech respectively. The results were concordant between 2 assays for more than one MSA in only 3 patients. The three combinations of these patients were anti-Jo-1 and anti-NXP-2, anti-Jo-1 and anti-TIF1-gamma, and anti-SAE and anti-NXP2 autoantibodies. The first two patients had an antisynthetase syndrome and the last patient an overlap myositis phenotype. All assays combined, anti-TIF1-gamma (9/19), anti-Jo-1 (7/19) and anti-NXP2 (6/19) autoantibodies were the most detected MSAs with concurrent detection of another MSA, though concordance between assays for these MSAs was low to moderate. Conclusion: Detection of coexisting MSAs with LIA or DIA occurs in a minority of patients with IIM with varying prevalence between assays from different manufacturers. The combination of more than 1 MSA is not concordant between LIAs/DIAs in the vast majority of patients, suggesting that in most patients detection of coexisting MSAs with LIAs/DIAs reflects a problem of specificity of the assays for the involved autoantibodies. References: [1] McHugh NJ, Tansley SL. Autoantibodies in myositis. Nature Reviews Rheumatology. 2018. [2] Brouwer R, Hengstman GJD, Egberts V, Ehrfeld H, Bozic B, Ghirardello a, et al. Autoantibody profiles in the sera of European patients with myositis. Ann Rheum Dis. 2001;60:116–23. [3] Cavazzana I, Fredi M, Ceribelli a, Mordenti C, Ferrari F, Carabellese N, et al. Testing for myositis specific autoantibodies: Comparison between line blot and immunoprecipitation assaysin57myositis sera. J Immunol Methods. 2016; Acknowledgement: The study was funded by alphadia, D-tek, Trinity Biotech and Euroimmun. Disclosure of interests: Jean-Baptiste Vulsteke Grant/research support from: SB PhD Fellow at FWO, grant from the Fund Joël Hurlet, Xavier Bossuyt Consultant for: inova Diagnostics, Kristl G Claeys: None declared, Doreen Dillaerts: None declared, Nele Vanhorebeek: None declared, Koen Poesen: None declared, Jan Lenaerts: None declared, Rene Westhovens Grant/research support from: Bristol-Myers Squibb, Consultant for: Celltrion, Galapagos-Gilead, Philip Van Damme Grant/research support from: Senior clinical investigatorship at FWO-Vlaanderen, Daniel Blockmans: None declared, Petra De Haes: None declared, Ellen De Langhe: None declared